Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11606-021-06999-9
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility Index for Assessing the Robustness of the Statistically Significant Results of Experimental Clinical Studies

Abstract: I n a randomized controlled trial (RCT) comparing treatments A and B, a null hypothesis (H 0 ) of no difference in a primary outcome of interest is defined. Whether any observed difference is statistically significant has traditionally been based on the P value and the confidence interval (CI). For a century, an arbitrary threshold of 0.05 (1/20) has been used to define statistical significance. 1 Because this probability is quite low, we conclude that P ≤ 0.05 suggests that the observed difference between A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…For the outcomes included in this analysis, the median FI was 2.5 (IQR 2-4), the mean FI was 2.9 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 10 14 , 17 , 18 , 21 , 23 , 29 31 , 36 , 38 , 42 , 47 53 , 55 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the outcomes included in this analysis, the median FI was 2.5 (IQR 2-4), the mean FI was 2.9 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 10 14 , 17 , 18 , 21 , 23 , 29 31 , 36 , 38 , 42 , 47 53 , 55 …”
Section: Discussionsupporting
confidence: 92%
“…These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 1014,17,18,21,23,29 31,36,38,42,47 53,55 57 and FQ of 0.048. 1012,18,21,…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, only 2 prior studies have written about the CFI and CFQ. Caldwell et al 5 reported a CFI of 9 for 39 nondichotomous outcomes in the sports medicine and arthroscopy literature, and Ho et al 15 calculated a CFI of 3 for a single RCT investigating vagal nerve electrical stimulation after stroke. The present study is thereby the first to thoroughly assess statistical fragility for a specific orthopaedic intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although fragility index is an increasingly popular metric to allegedly show the robustness of trial results, it has also been referred to as a p value in disguise and a potentially misleading metric. 4 In the hypothetical case regarding patients who withdrew consent, McGuire and colleagues could have calculated that 226 events in 567 patients in the awake prone positioning group and 257 events in 559 patients in the control group yields a p value of 0·041 with a Fisher's exact test. We must stress that the robustness of a study relies on its design, study implementation, analysis plan, effect sizes, CIs, generalisability, and limitations, and not on a single integer derived from an inappropriate secondary analysis of a hypothetical randomised trial that never occurred.…”
mentioning
confidence: 99%